Феномен української гімнастки Ніни Бочарової - Ковальчук, Надія Миколаївна; Усачов, Віктор Миколайович (УДУ імені Михайла Драгоманова, 2025)
Українські гімнастки вписали яскраву сторінку в історію виступів радянських спортсменів. Серед них була і Ніна Антонівна Бочарова – дворазова олімпійська чемпіонка XV Літніх Ігор у Гельсінкі 1952 р. у вправах на колоді та у командній першості; володарка срібних олімпійських медалей в багатоборстві та у командній вправі з предметом; чемпіонка світу 1954 р. у командній першості та у командних вправах з обручем; абсолютна чемпіонка СРСР 1949 і 1951 рр., чотириразова чемпіонка СРСР в окремих видах багатоборства. Ніну Бочарову з її унікальними досягненнями незаслужено забули на кілька десятиліть. І тільки у 80-90-их рр. відбулося повернення імені цієї людини до історії спорту, а на початку 2000-их рр. розпочалося гідне пошанування спортсменки Метою дослідження: розширення бази даних про першу олімпійську чемпіонку України Ніну Антонівну Бочарову та висвітлення її феномену у гімнастиці. Аналіз та узагальнення науково-методичної, спеціальної літератури, довідників, інтернет-ресурсів, фото- та відеоматеріалів дають право стверджувати, що Н.А. Бочарова була унікальною гімнасткою, достойною олімпійської нагороди.

Ukrainian gymnasts wrote a bright page in the history of Soviet athletes' performances. Among them was Nina Bocharova: two-time Olympic champion of the XV Summer Games in Helsinki in 1952 in balance beam exercises and in the team championship; winner of Olympic silver medals in the all-around and in the team exercise with an object; world champion in the team championship and in the team exercises with a hoop in 1954; absolute champion of the USSR in 1949 and 1951, four-time champion of the USSR in certain types of all-around. Nina Bocharova with her unique achievements was undeservedly forgotten for several decades. And only in the 80-90s the name of this person returned to the history of sports, and at the beginning of the 2000s a dignified tribute to the sportswoman began. The purpose of the study: to expand the database on the first Olympic champion of Ukraine Nina Bocharova and to highlight her phenomenon in gymnastics. Analysis and generalization of scientific and methodological, special literature, reference books, Internet resources, photo and video materials give the right to assert that N. Bocharova was a unique gymnast, worthy of an Olympic award. Nina Bocharova from childhood was tempered by difficult life trials, despite all obstacles, did not lose her love for gymnastics, trained hard and went towards her goal. The goal of life of the famous champion was to defeat herself. Olympic champion Nina Bocharova was a graceful Ukrainian woman with an iron will and strong character, bold and fearless, creative, until her old age she was devoted to sports, trained the younger generation, was active in the Olympic Academy of Ukraine, and supported the sports authority of our state.
Keywords: вправи на колоді; вправи на брусах; змагання; Ігри ХV Олімпіади 1952р. у Гельсінкі; олімпійська чемпіонка; спортивна гімнастика; beam exercises; uneven bars exercises; competitions; Games of the XV Olympiad in 1952 in Helsinki; Olympic champion; artistic gymnastics; Ukraine; 796.41.071(477)(092)